Optimalisasi Metode Al-Miftah Lil Ulum dalam Pembelajaran Nahwu di Madrasah Tsanawiyah Ummul Qura Amuntai - Muhammad Majdi; Nor Mahmudah; Maulida Maulida (Madrasah: Jurnal Pendidikan Madrasah, 2026)
For several years, the teaching of nahwu (Arabic grammar) at Madrasah Tsanawiyah Ummul Qura Amuntai has implemented the Al-Miftah Lil Ulum method to enhance the effectiveness of learning. In its implementation, students are able to follow the lessons enthusiastically and demonstrate improvement in understanding Arabic grammatical rules. This study aims to describe and analyze the effectiveness of the Al-Miftah Lil Ulum method in nahwu learning at Madrasah Tsanawiyah Ummul Qura Amuntai. The research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The study was conducted in one day during a face-to-face nahwu learning session. The results show that the implementation of the Al-Miftah Lil Ulum method is active and enjoyable, covering three stages of learning: introduction, core activity, and closing. The teacher acts as a facilitator who guides students to understand Arabic sentence patterns in a gradual and systematic way. With an interactive and contextual learning atmosphere, students find it easier to grasp the material and are motivated to participate actively. Overall, the implementation of the Al-Miftah Lil Ulum method is considered effective in improving students’ motivation and learning outcomes in nahwu learning at the school.